Tubeimoside I Ameliorates Myocardial Ischemia-Reperfusion Injury through SIRT3-Dependent Regulation of Oxidative Stress and Apoptosis. (9th November 2021) - Lv, Dingyi; Luo, Minghao; Cheng, Zhe; Wang, Ruiyu; Yang, Xiyang; Guo, Yongzheng; Huang, Longxiang; Li, Xiang; Huang, Bi; Shen, Jian; Luo, Suxin; Yan, Jianghong
Abstract : Myocardial ischemia-reperfusion injury (MIRI) is a phenomenon that reperfusion leads to irreversible damage to the myocardium and increases mortality in acute myocardial infarction (AMI) patients. There is no effective drug to treat MIRI. Tubeimoside I (TBM) is a triterpenoid saponin purified from Chinese traditional medicine tubeimu. In this study, 4 mg/kg TBM was given to mice intraperitoneally at 15 min after ischemia. And TBM treatment improved postischemic cardiac function, decreased infarct size, diminished lactate dehydrogenase release, ameliorated oxidative stress, and reduced apoptotic index. Notably, ischemia-reperfusion induced a significant decrease in cardiac SIRT3 expression and activity, while TBM treatment upregulated SIRT3's expression and activity. However, the cardioprotective effects of TBM were largely abolished by a SIRT3 inhibitor 3-(1H-1, 2, 3-triazol-4-yl) pyridine (3-TYP). This suggests that SIRT3 plays an essential role in TBM's cardioprotective effects. In vitro, TBM also protected H9c2 cells against simulated ischemia/reperfusion (SIR) injury by attenuating oxidative stress and apoptosis, and siSIRT3 diminished its protective effects. Taken together, our results demonstrate for the first time that TBM protects against MIRI through SIRT3-dependent regulation of oxidative stress and apoptosis. TBM might be a potential drug candidate for MIRI treatment.